Handball injuries during major international tournaments - Langevoort, G.; Myklebust, G.; Dvorak, J.; Junge, A. (Scandinavian Journal of Medicine & Science in Sports, 2007)
Background: Several authors have analyzed the incidence of handball injuries in amateur players but information of handball injury in top-level players is very limited. The aim of the study was to analyze the incidence, circumstances and characteristics of handball injuries during major international tournaments.